A composite material and its preparation method and use

Through chemical vapor deposition and 3D printing technology, the two-dimensional material film and polymer layer are alternately stacked and rolled, solving the problem of poor dispersion of two-dimensional materials in three-dimensional composite materials, and significantly improving the mechanical and electrical properties of the composite materials.

CN114248444BActive Publication Date: 2025-01-07THE NAT CENT FOR NANOSCI & TECH NCNST OF CHINA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111569458.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-21
Publication Date
2025-01-07
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

The prior art is difficult to evenly disperse two-dimensional materials into three-dimensional composite materials, resulting in limited improvement in the mechanical and electrical properties of the composite materials, and the preparation method is complex and costly.

Method used

A two-dimensional material film is grown by chemical vapor deposition method, coated with a polymer layer, formed composite wires by transverse shear rolling, and evenly dispersed into the three-dimensional structure by 3D printing, ensuring the integrity and continuity of the two-dimensional material.

Benefits of technology

The uniform dispersion of two-dimensional materials in the composite material is achieved, the mechanical and electrical properties of the composite material are improved, and the preparation method simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114248444B_ABST
    Figure CN114248444B_ABST
Patent Text Reader

Abstract

The present invention provides a composite material and a preparation method and use thereof. The preparation method comprises the following steps: (1) growing a two-dimensional material on a substrate by chemical vapor deposition to obtain a two-dimensional material film; (2) coating a polymer on the surface of the two-dimensional material film away from the substrate to obtain a composite film comprising a two-dimensional material film and a polymer layer; shearing and rolling the composite film transversely to obtain a composite wire; (3) 3D printing the composite wire to obtain the composite material; the composite material obtained by the preparation method provided by the present invention has a specific configuration and function; the preparation method can make the two-dimensional film material uniformly dispersed in the three-dimensional composite material, and can improve the mechanical or electrical properties of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a composite material and a preparation method and application thereof. Background Art

[0002] Two-dimensional materials refer to materials in which electrons can move freely only in two dimensions at the nanoscale. Due to their unique properties, two-dimensional materials are often added to polymers to prepare high-performance materials. Among them, graphene is the earliest two-dimensional material to be isolated. It is a kind of carbon atom in the form of sp 2 The two-dimensional carbon nanomaterials composed of hybrid orbitals in a hexagonal honeycomb lattice structure have high strength and good electrical and thermal conductivity, and are widely used in semiconductors, electronic appliances, energy, composite materials, etc. Especially in the field of composite materials, graphene is suitable for the development of low-weight and high-performance composite materials due to its advantages such as good elasticity, large specific surface area, high Young's modulus and fracture strength.

[0003] One of the methods in the prior art is to disperse graphene oxide in a suitable high-viscosity polymer material or other material to form a slurry, and then process it to obtain the required material. For example, CN106946581A discloses a method for preparing a conductive graphene / inorganic polymer composite material. The method is to mix a continuous fiber reinforced inorganic polymer-based composite material with a graphene oxide solution, and then process it into a shape. However, in the method, phase separation and aggregation of graphene sheets in a polymer matrix will seriously affect its dispersion efficiency, and the method has high requirements for slurry viscosity.

[0004] CN109401237A discloses a method for preparing a composite material. The preparation method comprises: reacting aramid staple fibers with graphene oxide to obtain aramid staple fibers with graphene loaded on the surface; then mixing polyacrylate emulsion, latex, the aramid staple fibers and carrier resin, extruding and granulating to obtain the graphene toughening masterbatch. The graphene toughening masterbatch is mixed with polylactic acid and extruded to obtain the composite material. Although the preparation method improves the performance of polylactic acid to a certain extent, the dispersibility of the graphene toughening masterbatch prepared by the method in the matrix needs to be further improved, and the method introduces many components, which increases the cost.

[0005] In addition, graphene composite materials can also be prepared by electrostatic spinning. For example, CN105755675A discloses a kind of enhanced heat-resistant polylactic acid electrostatic spinning fiber film and its preparation method. The electrostatic spinning fiber film includes polylactic acid matrix resin and composite reinforcing agent, and the composite reinforcing agent is a graphene oxide sheet of surface-loaded zeolite imidazolate skeleton ZIF-8. The fiber film is blended with a polylactic acid solution and a composite reinforcing agent, and then prepared by electrostatic spinning under certain process conditions. Compared with pure polylactic acid fiber film, the tensile strength and elongation at break of polylactic acid fiber film are significantly improved. However, in the method, graphene exists in the form of fragments, and the performance improvement is small.

[0006] Therefore, developing a method for preparing composite materials so that two-dimensional continuous film materials can be evenly dispersed into a three-dimensional composite material structure, and the performance of the resulting composite material is greatly improved, which can be used to prepare various components with high conductivity or mechanical enhancement is an urgent problem to be solved in this field. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a composite material and its preparation method and use. The preparation method provided by the present invention can evenly disperse nanoscale two-dimensional membrane materials into three-dimensional polymer components, thereby improving the mechanical and electrical properties of the composite material.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a composite material, the preparation method comprising the following steps:

[0010] (1) growing a two-dimensional material on a substrate by chemical vapor deposition to obtain a two-dimensional material film;

[0011] (2) coating a polymer on the surface of the two-dimensional material film away from the substrate to obtain a composite film comprising a two-dimensional material film and a polymer layer; and transversely shearing and rolling the composite film to obtain a composite wire;

[0012] (3) 3D printing the composite wire to obtain the composite material.

[0013] In the present invention, the preparation method can obtain a large-area, continuous two-dimensional material through chemical vapor deposition, and obtain a composite film including a two-dimensional material film and a polymer layer by coating a polymer on the two-dimensional material. The composite film is then transversely sheared and rolled into a composite wire, and the composite material is obtained by 3D printing. The preparation method can evenly disperse the nanoscale two-dimensional material in the polymer, and the two-dimensional material will not aggregate in the polymer during 3D printing. On the one hand, the orientation of the two-dimensional material in the composite wire is increased and the disordered arrangement of the two-dimensional material is reduced. On the other hand, the integrity and continuity of the two-dimensional film material are maximized, which is not available in traditional small-layer dispersed materials. In addition, the obtained composite material has a controllable three-dimensional configuration, and its conductivity and mechanical properties are greatly improved.

[0014] Preferably, the substrate comprises a metal substrate or a non-metal substrate.

[0015] Preferably, the material of the metal substrate includes any one of copper, nickel, iron, cobalt or platinum, or a combination of at least two of the metals.

[0016] Preferably, the metal substrate comprises a copper substrate.

[0017] The length of the metal substrate in the present invention is 10 to 15 cm, for example, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc.

[0018] Preferably, the width of the metal substrate is 10-15 cm, for example, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc.

[0019] Preferably, the material of the non-metal substrate includes silicon oxide and / or mica flakes.

[0020] Preferably, the material of the non-metal substrate includes silicon oxide and mica flakes.

[0021] The length of the non-metallic substrate in the present invention is 10 to 15 cm, for example, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc.

[0022] Preferably, the width of the non-metallic substrate is 10 to 15 cm, for example, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc.

[0023] Preferably, the two-dimensional material includes any one of graphene, boron nitride or transition metal sulfide, or a combination of at least two of them.

[0024] Preferably, the two-dimensional material is graphene, and the raw material used in the chemical vapor deposition method includes any one of a solid carbon source, a liquid carbon source or a gaseous carbon source, or a combination of at least two of them, and is more preferably a gaseous carbon source.

[0025] Preferably, the gaseous carbon source includes any one of methane, acetylene, ethylene, ethane or propane, or a combination of at least two of them.

[0026] Preferably, the two-dimensional material is boron nitride, and the raw materials used in the chemical vapor deposition method include a boron source and a nitrogen source.

[0027] Preferably, the boron source includes any one of borazine, borane, ammonia borane, decaborane or diborane, or a combination of at least two thereof.

[0028] Preferably, the nitrogen source comprises ammonia and / or ammonia borane.

[0029] Preferably, the two-dimensional material is a transition metal sulfide, and the raw materials used in the chemical vapor deposition method include transition metal oxides and sulfur.

[0030] Preferably, the transition metal oxide comprises molybdenum oxide and / or tungsten oxide.

[0031] Preferably, the equipment for growing two-dimensional materials is a tube furnace.

[0032] Preferably, the growth temperature is 700-1100°C, for example, 700°C, 800°C, 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C, 1100°C, etc.

[0033] Preferably, the growth time is 10 to 30 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc.

[0034] Preferably, the growth pressure is 20-101325Pa, for example, 20Pa, 50Pa, 100Pa, 200Pa, 500Pa, 800Pa, 1000Pa, 101325Pa, etc.

[0035] Preferably, the growth atmosphere comprises argon and / or hydrogen.

[0036] Preferably, the thickness of the two-dimensional material film is 0.3-1 nm, for example, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, etc.

[0037] Preferably, the two-dimensional material film includes a single layer or at least two layers of two-dimensional material.

[0038] Preferably, the number of layers of the two-dimensional material in the two-dimensional material film is one, two or three.

[0039] Preferably, the two-dimensional material film includes a graphene film.

[0040] Preferably, the thickness of the single-layer graphene film is 0.3-0.4 nm, for example, 0.3 nm, 0.35 nm, 0.4 nm, etc.

[0041] Preferably, the polymer includes any one of polylactic acid, polyacrylonitrile, acrylonitrile-butadiene-styrene copolymer (ABS), polyamide, polymethyl methacrylate or polycarbonate, or a combination of at least two thereof.

[0042] In the present invention, the polymer is preferably polylactic acid.

[0043] Preferably, the polymer is applied in the form of a polymer dispersion.

[0044] Preferably, the solvent of the polymer dispersion comprises dichloromethane.

[0045] Preferably, the solid content of the polymer dispersion is 1.7-3%, for example, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% and the like.

[0046] Preferably, the coating method is spin coating.

[0047] Preferably, the spin coating device is a centrifugal coater.

[0048] Preferably, the rotation speed of the centrifugal glue homogenizer is 1300-8000r / min, for example, it can be 1300r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min, 3500r / min, 4000r / min, 4500r / min, 5000r / min, 5500r / min, 6000r / min, 6500r / min, 7000r / min, 7500r / min, 8000r / min, etc.

[0049] Preferably, the spin coating time is 10 to 60 s, for example, 10 s, 20 s, 30 s, 40 s, 50 s, 60 s, etc.

[0050] Preferably, the thickness of the polymer layer in the composite film is 50 to 500 nm, for example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc., more preferably 200 to 300 nm.

[0051] Preferably, after obtaining the polymer layer, the step of removing the substrate is further included.

[0052] Preferably, the method of removing the substrate includes removing it by an etching solution.

[0053] Preferably, the solute of the etching solution includes any one of sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, ferric chloride, ferric nitrate or ammonium persulfate, or a combination of at least two thereof.

[0054] Preferably, the concentration of the etching solution is 0.1-1 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc.

[0055] In the present invention, after the substrate is removed by etching solution, the method further comprises the step of washing the composite film in aqueous solution.

[0056] Preferably, the composite wire is obtained by laminating at least two layers of the composite film and then shearing and rolling them transversely.

[0057] Preferably, the composite wire is obtained by stacking 30 to 40 layers of the composite film and then shearing and rolling them transversely. The number of layers of the composite film can be, for example, 30 layers, 32 layers, 34 layers, 36 layers, 38 layers, 40 layers, etc.

[0058] In the present invention, when the number of layers of the composite film is greater than 40, it is not conducive to the evaporation of water during the hot pressing process, thereby causing the existence of pores, affecting the dispersion of the two-dimensional material and the performance of the composite material.

[0059] Preferably, the diameter of the composite wire is 1.4-1.75 mm, for example, it can be 1.4 mm, 1.42 mm, 1.44 mm, 1.46 mm, 1.48 mm, 1.5 mm, 1.54 mm, 1.58 mm, 1.6 mm, 1.62 mm, 1.64 mm, 1.68 mm, 1.7 mm, 1.72 mm, 1.74 mm, etc.

[0060] Preferably, the length of the composite wire is 7 to 20 cm, for example, 7 cm, 10 cm, 12 cm, 14 cm, 16 cm, 18 cm, 20 cm, etc.

[0061] In the present invention, the thickness of the composite material is 0.2-0.5 mm, for example, it can be 0.2 mm, 0.22 mm, 0.24 mm, 0.26 mm, 0.28 mm, 0.3 mm, 0.32 mm, 0.34 mm, 0.36 mm, 0.38 mm, 0.4 mm, 0.42 mm, 0.44 mm, 0.46 mm, 0.48 mm, 0.5 mm, etc.

[0062] Preferably, the width of the composite material is 1-2 mm, for example, 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2 mm, etc.

[0063] Preferably, the length of the composite material is 7-8 mm, for example, 7 mm, 7.2 mm, 7.4 mm, 7.6 mm, 7.8 mm, 8 mm, etc.

[0064] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0065] (1) growing a two-dimensional material on a substrate by chemical vapor deposition at 700 to 1100° C. for 10 to 30 minutes to obtain a two-dimensional material film with a thickness of 0.3 to 1.0 nm;

[0066] (2) Spin-coating a polymer dispersion onto a surface of the two-dimensional material film away from the substrate, and removing the substrate with an etching solution to obtain a composite film comprising a two-dimensional material film and a polymer layer; the thickness of the polymer layer is 50 to 500 nm; stacking 30 to 40 layers of the composite film and performing transverse shear rolling to obtain a composite wire having a diameter of 1.4 to 1.75 mm and a length of 7 to 20 cm;

[0067] (3) 3D printing the composite wire to obtain the composite material.

[0068] The method of stacking 30 to 40 layers of the composite membranes described in the present invention includes: using a single-layer composite membrane containing a substrate to scoop up other composite membranes with the substrate removed in an aqueous solution, and after drying, continue to scoop up the next layer to finally obtain a stacked composite membrane, and then remove the substrate through an etching solution, dry, and obtain a stacked composite membrane.

[0069] In the present invention, the transverse shear rolling refers to folding the stacked composite films to a certain width and thickness and then rolling and curling them to obtain the composite wire.

[0070] Preferably, the certain width is 2-4 mm, for example, 2 mm, 3 mm, 4 mm, etc.

[0071] Preferably, the certain thickness is 2-4 mm, for example, 2 mm, 3 mm, 4 mm, etc.

[0072] In a second aspect, the present invention provides a composite material, wherein the composite material is prepared by the preparation method described in the first aspect.

[0073] In the present invention, the composite material is a composite material with a specific structure and function; the two-dimensional membrane material is uniformly distributed in the composite material, and the configuration of the composite material is controllable.

[0074] In a third aspect, the present invention provides a use of the composite material according to the second aspect in the fields related to three-dimensional structural mechanics and electricity.

[0075] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0076] Compared with the prior art, the present invention has the following beneficial effects:

[0077] The preparation method of the composite material provided by the present invention obtains a two-dimensional material film with good continuity through a chemical vapor deposition method, and uniformly disperses the two-dimensional material film into a three-dimensional composite component with controllable structure through alternate stacking of the two-dimensional material and the polymer through 3D printing, thereby increasing the orientation degree of the two-dimensional material in the composite material and reducing the disordered arrangement of the two-dimensional material; maximally ensuring the integrity and continuity of the two-dimensional film material; and the obtained composite material has greatly improved three-dimensional configuration controllability, conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 A stress-strain curve diagram of the composite material provided in Example 1;

[0079] Figure 2 A scanning electron microscope image of the composite material provided in Example 1;

[0080] Figure 3 A stress-strain curve diagram of the composite material provided for Comparative Example 1;

[0081] Figure 4 A scanning electron microscope image of the composite material provided for Comparative Example 1;

[0082] Figure 5 A partial enlarged view of the composite material provided for Comparative Example 1;

[0083] Figure 6 A stress-strain curve diagram of the composite material provided for Comparative Example 2;

[0084] Figure 7 A stress-strain curve diagram of the composite material provided for Comparative Example 3;

[0085] Figure 8 A stress-strain curve diagram of the composite material provided for Comparative Example 4;

[0086] Fig. 9 A scanning electron microscope image of the composite material provided for Comparative Example 4;

[0087] Fig.10 This is a partial enlarged view of the composite material provided for Comparative Example 4. DETAILED DESCRIPTION

[0088] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0089] Example 1

[0090] This embodiment provides a composite material and a preparation method thereof, and the specific steps are as follows:

[0091] (1) growing graphene on a copper substrate having a length and width of 13 cm for 20 min in a tube furnace with CH4 as a carbon source at a temperature of 1045° C. to obtain a graphene film having a thickness of 0.34 nm; the graphene film comprising a single layer of graphene;

[0092] (2) Spinning a polylactic acid dispersion having a solid content of 1.7% (polylactic acid purchased from Aurora Elvo, brand PLA-1.75mm, and the solvent is dichloromethane) on the surface of the graphene film away from the copper substrate by a centrifugal coater with a rotation speed of 4000 r / min, spin coating for 30 seconds, and after drying, etching and removing the copper substrate by a 0.5 mol / L ammonium persulfate solution to obtain a composite film comprising a graphene film and a polylactic acid layer, wherein the thickness of the polylactic acid layer is 200 to 300 nm; stacking 40 layers of the composite film and performing transverse shear rolling to obtain a composite wire having a diameter of 1.75 mm and a length of 13 cm;

[0093] (3) The composite wire is 3D printed using an A6 printer to obtain a composite material with a thickness of 0.5 mm, a width of 2 mm, and a length of 8 mm.

[0094] The stress-strain curve of the composite material was tested by a horizontal tensile testing machine (HY-0230), and the obtained stress-strain curve was as shown in Figure 1 The cross-sectional morphology of the composite material was tested by scanning electron microscopy (SEM, instrument model: Hitachi-SU8220), and the obtained scanning electron microscope image was as shown in Figure 2 shown.

[0095] Example 2

[0096] This embodiment provides a method for preparing a composite material, which differs from Embodiment 1 only in that in step (1), molybdenum oxide and sulfur are used as raw materials to grow molybdenum sulfide on a substrate, and the other steps and parameters are the same as those in Embodiment 1.

[0097] Example 3

[0098] This embodiment provides a method for preparing a composite material, which differs from Embodiment 1 only in that in step (1), tungsten oxide and sulfur are used as raw materials to grow tungsten sulfide on a substrate, and the other steps and parameters are the same as those in Embodiment 1.

[0099] Example 4

[0100] This embodiment provides a method for preparing a composite material, which differs from Embodiment 1 only in that in step (2), the polylactic acid dispersion is replaced by an acrylonitrile-butadiene-styrene copolymer dispersion (Aurora Elvo, brand ABS-B 1.75mm) of the same concentration, and the other steps and parameters are the same as those in Embodiment 1.

[0101] Comparative Example 1

[0102] This comparative example provides a composite material and a preparation method thereof, and the specific steps are as follows:

[0103] (1) Spinning a polylactic acid dispersion having a solid content of 1.7% on a copper substrate having a length and width of 13 cm by a centrifugal coater at 4000 r / min for 30 seconds, and after drying, etching the copper substrate with a 0.5 mol / L ammonium persulfate solution to obtain a composite film including a polylactic acid layer, wherein the thickness of the polylactic acid layer is 200 to 300 nm; stacking 40 layers of the composite film and performing transverse shear rolling to obtain a composite wire having a diameter of 1.7 mm and a length of 12 cm; the solvent of the polylactic acid dispersion is dichloromethane;

[0104] (2) The composite wire is 3D printed using an A6 printer to obtain a composite material with a thickness of 0.5 mm, a width of 2 mm, and a length of 8 mm.

[0105] The stress-strain curve and morphology of the composite material were tested using the same method as in Example 1. The obtained stress-strain curve is shown in FIG. Figure 3 As shown in the scanning electron microscope image Figure 4 and Figure 5 shown.

[0106] Comparative Example 2

[0107] This comparative example provides a composite material and a preparation method thereof, and the specific steps are as follows:

[0108] (1) A polylactic acid dispersion having a solid content of 1.7% is spin-coated on a copper substrate having a length and width of 13 cm by a centrifugal coater at a rotation speed of 4000 r / min for 30 seconds. After drying, an ethanol solution of graphene oxide having a concentration of 0.01 mg / mL is applied to the surface of the polylactic acid layer away from the copper substrate. After the ethanol is completely evaporated, the copper substrate is removed by etching with an ammonium persulfate solution having a concentration of 0.5 mol / L to obtain a composite film comprising a polylactic acid layer and a graphene oxide film, wherein the thickness of the polylactic acid layer is 200-300 nm, and the thickness of the graphene oxide film is 200-300 nm; 40 layers of the composite film are stacked and then subjected to transverse shear rolling to obtain a composite wire having a diameter of 1.74 mm and a length of 13 cm; the solvent of the polylactic acid dispersion is dichloromethane;

[0109] (3) The composite wire is 3D printed using an A6 printer to obtain a composite material with a thickness of 0.5 mm, a width of 2 mm, and a length of 8 mm.

[0110] The stress-strain curve of the composite material was tested by the same method as in Example 1. The obtained stress-strain curve is shown in FIG. Figure 6 shown.

[0111] Comparative Example 3

[0112] This comparative example provides a method for preparing a composite material, which differs from comparative example 2 only in that the concentration of the graphene oxide ethanol solution is 0.02 mg / mL, and the other steps and parameters are the same as those in comparative example 2.

[0113] The stress-strain curve of the composite material was tested by the same method as in Example 1. The obtained stress-strain curve is shown in FIG. Figure 7 shown.

[0114] Comparative Example 4

[0115] This comparative example provides a method for preparing a composite material, which differs from comparative example 2 only in that the concentration of the graphene oxide ethanol solution is 0.04 mg / mL, and the other steps and parameters are the same as those in comparative example 2.

[0116] The stress-strain curve of the composite material was tested by the same method as in Example 1. The obtained stress-strain curve is shown in FIG. Figure 8 As shown in the scanning electron microscope image Fig. 9 and Fig.10 shown.

[0117] Performance Testing

[0118] (1) Elastic modulus: E = (F / S) / (ΔL / L), where F is the tensile force applied to the print, S is the cross-sectional area of ​​the print, ΔL is the elongation of the print, L is the original length of the print, and E is the elastic modulus of the print.

[0119] (2) Tensile strength: Tensile strength is also the maximum load-bearing capacity of the printed part under static tensile conditions. max .

[0120] The specific test results are shown in Table 1:

[0121] Table 1

[0122] Elastic modulus (MPa) Tensile strength(MPa) Example 1 340 39 Example 2 288 35 Example 3 290 34 Example 4 240 29 Comparative Example 1 215 19.8 Comparative Example 2 230 25.2 Comparative Example 3 288 31.4 Comparative Example 4 300 36.5

[0123] As can be seen from the above table, the preparation method of the composite material provided by the present invention is to first grow a two-dimensional material by chemical vapor deposition to obtain a two-dimensional material film with good continuity, and the number of layers of the grown two-dimensional material can be controlled; then a composite film is obtained by coating a polymer onto the two-dimensional material film; multiple layers of the composite film are stacked and then transversely sheared and rolled to obtain a composite wire, and a composite material with excellent mechanical properties is obtained by 3D printing.

[0124] It can be seen from Examples 1 to 4 that the elastic modulus of the composite material is 240-340 MPa, and the tensile strength is 29-39 MPa; and by comparing Example 1 with Examples 2 to 4, it can be seen that when the two-dimensional material is graphene and the polymer is polylactic acid, the elastic modulus and tensile strength of the composite material are the best; by comparing Example 1 with Comparative Examples 1 to 4, it can be seen that when graphene is not added to the composite material and graphene is not grown by chemical vapor deposition, the elastic modulus or tensile properties of the obtained composite material decrease.

[0125] In summary, the present invention grows two-dimensional materials through chemical vapor deposition to obtain a two-dimensional material film, and the two-dimensional material film is alternately overlapped with a polymer layer, rolled to form a wire, and a composite material is obtained by 3D printing, so that the two-dimensional material is evenly dispersed in the composite material, and the obtained composite material has excellent mechanical properties.

[0126] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite material, characterized in that: The preparation method comprises the following steps: (1) growing a two-dimensional material on a substrate by chemical vapor deposition to obtain a two-dimensional material film; (2) coating a polymer on the surface of the two-dimensional material film away from the substrate to obtain a composite film comprising a two-dimensional material film and a polymer layer; and transversely shearing and rolling the composite film to obtain a composite wire; (3) performing 3D printing on the composite wire to obtain the composite material; The thickness of the two-dimensional material film is 0.3 to 0.9 nm; The two-dimensional material film includes a single layer or two layers of two-dimensional material; The substrate is a copper substrate; and the polymer is polylactic acid.

2. The preparation method according to claim 1, characterized in that: The two-dimensional material includes any one of graphene, boron nitride or transition metal sulfide, or a combination of at least two of them.

3. The preparation method according to claim 2, characterized in that: The two-dimensional material is graphene, and the raw material used in the chemical vapor deposition method includes any one of a solid carbon source, a liquid carbon source or a gaseous carbon source, or a combination of at least two of them.

4. The preparation method according to claim 3, characterized in that: The raw material used in the chemical vapor deposition method is a gas phase carbon source.

5. The preparation method according to claim 4, characterized in that: The gaseous carbon source includes any one of methane, acetylene, ethylene, ethane or propane, or a combination of at least two of them.

6. The preparation method according to claim 2, characterized in that: The two-dimensional material is boron nitride, and the raw materials used in the chemical vapor deposition method include a boron source and a nitrogen source.

7. The preparation method according to claim 6, characterized in that: The boron source includes any one of cycloborazine, borane, ammonia borane, decaborane or diborane, or a combination of at least two thereof.

8. The preparation method according to claim 6, characterized in that: The nitrogen source includes ammonia and / or ammonia borane.

9. The preparation method according to claim 2, characterized in that: The two-dimensional material is a transition metal sulfide, and the raw materials used in the chemical vapor deposition method include transition metal oxides and sulfur.

10. The preparation method according to claim 9, characterized in that: The transition metal oxide includes molybdenum oxide and / or tungsten oxide.

11. The preparation method according to claim 1, characterized in that: The equipment for growing two-dimensional materials is a tubular furnace.

12. The preparation method according to claim 1, characterized in that: The growth temperature is 700-1100°C.

13. The preparation method according to claim 1, characterized in that: The growth time is 10 to 30 minutes.

14. The preparation method according to claim 1, characterized in that: The growth pressure is 20-101325Pa.

15. The preparation method according to claim 1, characterized in that: The growth atmosphere includes argon and / or hydrogen.

16. The preparation method according to claim 1, characterized in that: The two-dimensional material film includes a graphene film.

17. The preparation method according to claim 16, characterized in that: The thickness of the single-layer graphene film is 0.3-0.4 nm.

18. The preparation method according to claim 1, characterized in that: The polymer is applied in the form of a polymer dispersion.

19. The preparation method according to claim 18, characterized in that: The solvent of the polymer dispersion includes dichloromethane.

20. The preparation method according to claim 18, characterized in that: The solid content of the polymer dispersion is 1.7-3%.

21. The preparation method according to claim 18, characterized in that: The coating method is spin coating.

22. The preparation method according to claim 21, characterized in that: The spin coating device is a centrifugal coating machine.

23. The preparation method according to claim 22, characterized in that: The rotation speed of the centrifugal glue homogenizer is 1300-8000 r / min.

24. The preparation method according to claim 21, characterized in that: The spin coating time is 10 to 60 seconds.

25. The preparation method according to claim 1, characterized in that: The thickness of the polymer layer in the composite film is 50-500 nm.

26. The preparation method according to claim 25, characterized in that: The thickness of the polymer layer in the composite film is 200-300 nm.

27. The preparation method according to claim 1, characterized in that: After obtaining the polymer layer, the method further comprises the step of removing the substrate.

28. The preparation method according to claim 27, characterized in that: The method of removing the substrate includes removing it by etching solution.

29. The preparation method according to claim 28, characterized in that: The solute of the etching solution includes any one of sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, ferric chloride, ferric nitrate or ammonium persulfate, or a combination of at least two thereof.

30. The preparation method according to claim 28, characterized in that: The concentration of the etching solution is 0.1-1 mol / L.

31. The preparation method according to claim 1, characterized in that: The composite wire is obtained by laminating at least two layers of the composite film and then shearing and rolling them transversely.

32. The preparation method according to claim 31, characterized in that: The composite wire is obtained by stacking 30 to 40 layers of the composite film and then shearing and rolling them transversely.

33. The preparation method according to claim 1, characterized in that: The diameter of the composite wire is 1.4-1.75 mm.

34. The preparation method according to claim 1, characterized in that: The length of the composite wire is 7 to 20 cm.

35. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) growing a two-dimensional material on a substrate by chemical vapor deposition at 700 to 1100° C. for 10 to 30 minutes to obtain a two-dimensional material film with a thickness of 0.3 to 0.9 nm; (2) Spin-coating a polymer dispersion onto a surface of the two-dimensional material film away from the substrate, and removing the substrate with an etching solution to obtain a composite film comprising a two-dimensional material film and a polymer layer; the thickness of the polymer layer is 50 to 500 nm; stacking 30 to 40 layers of the composite film and performing transverse shear rolling to obtain a composite wire having a diameter of 1.4 to 1.75 mm and a length of 7 to 20 cm; (3) performing 3D printing on the composite wire to obtain the composite material; The two-dimensional material film includes a single layer or two layers of two-dimensional material; The substrate is a copper substrate; and the polymer is polylactic acid.

36. A composite material, characterized in that The composite material is prepared by the preparation method according to any one of claims 1 to 35.

37. Use of the composite material according to claim 36 in the fields related to three-dimensional structural mechanics and electricity.

Citation Information

Patent Citations

  • Reinforced heat-resistant polylactic acid electrostatic spun fibrous membrane and preparation method therefor

    CN105755675A

  • Method for preparing conductive graphene / inorganic polymer composite by adopting 3D printing technology

    CN106946581A

  • Graphene toughening masterbatch for polylactic acid three dimensionalprinted wire material and preparation method of graphene toughening masterbatch

    CN109401237A

  • Highly oriented carbon nano-tube / polymer composite film, and preparation method and application thereof

    CN102731949A

  • Method for preparing graphene-based flexible bionic sensing material through 3D printing

    CN112721147A